2017
DOI: 10.1242/jcs.194712
|View full text |Cite
|
Sign up to set email alerts
|

The LINC complex contributes to heterochromatin organisation and transcriptional gene silencing in plants

Abstract: The linker of nucleoskeleton and cytoskeleton (LINC) complex is an evolutionarily well-conserved protein bridge connecting the cytoplasmic and nuclear compartments across the nuclear membrane. While recent data support its function in nuclear morphology and meiosis, its involvement in chromatin organisation has not been studied in plants. Here, 3D imaging methods have been used to investigate nuclear morphology and chromatin organisation in interphase nuclei of the model plant Arabidopsis thaliana in which het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 81 publications
3
78
1
Order By: Relevance
“…(See Box 1 for expansion of abbreviated gene names used in this review.) In addition, the association of heterochromatin domains with the LINC (linker of nucleoskeleton and cytoskeleton) complex in the nuclear periphery is a spatial component that is relevant for heterochromatin silencing, as revealed using loss-of-function mutants [34]. The RdDM pathway, which relies on RNA Pol IV-dependent 24-nucleotide short interfering RNAs (siRNAs) [3537] and RNA Pol V-dependent RNAs [38], is crucial for both preserving the boundaries of heterochromatin domains and keeping TEs silent across generations [18, 3941].…”
Section: Genome Topographymentioning
confidence: 99%
“…(See Box 1 for expansion of abbreviated gene names used in this review.) In addition, the association of heterochromatin domains with the LINC (linker of nucleoskeleton and cytoskeleton) complex in the nuclear periphery is a spatial component that is relevant for heterochromatin silencing, as revealed using loss-of-function mutants [34]. The RdDM pathway, which relies on RNA Pol IV-dependent 24-nucleotide short interfering RNAs (siRNAs) [3537] and RNA Pol V-dependent RNAs [38], is crucial for both preserving the boundaries of heterochromatin domains and keeping TEs silent across generations [18, 3941].…”
Section: Genome Topographymentioning
confidence: 99%
“…Christophe Tatout (Université Clermont Auvergne, France) gave the final talk in the workgroup 1 session and outlined his work that focuses on developing NucleusJ, an ImageJ plugin for 3D analysis of nucleus images; it is now being improved and adapted to perform high-throughput 3D image analysis (Poulet et al, 2017) of different nuclear parameters, such as size and shape of the nucleus, and the position of heterochromatin structures within in the nucleus in whole-mount tissues. Efficient phenotyping tools are indispensable assets to evaluate the impact of loss of specific nuclear components, such as components of the nuclear periphery, on, for example, nuclear organisation and function.…”
Section: The Origins and Aims Of Indepthmentioning
confidence: 99%
“…Toward that goal, Poulet et al (2017a) have developed a 3D imaging protocol to query a number of aspects of nuclear and chromatin organization in Arabidopsis mutants of LINC complex components and related proteins. They found that chromocenters were preferentially associated with the nuclear periphery, but that this association and chromocenter compaction were changed in some mutants.…”
Section: The Nuclear Peripherymentioning
confidence: 99%
“…They found that chromocenters were preferentially associated with the nuclear periphery, but that this association and chromocenter compaction were changed in some mutants. Interestingly, transcriptional repression of heterochromatic repeat sequences was alleviated in some LINC mutants, suggesting that the Arabidopsis nuclear periphery is indeed involved in regulatory chromatin compaction (Poulet et al, 2017a).…”
Section: The Nuclear Peripherymentioning
confidence: 99%